The unheard voice: a qualitative exploration of companions' experiences of liaison psychiatry and mental health crises in the emergency department. (October 2019) - Collom, Jennifer; Patterson, Emma; Lawrence-Smith, Geoff; Tracy, Derek K.
Abstract : Aims and method: To understand the experience of companions of patients seen in the emergency department by liaison psychiatry teams. Participants were recruited via purposive sampling following a recent visit to the emergency department of an inner- or outer-London hospital. Semi-structured interviews were administered to all participants. Results: Two major themes were generated. The first concerned the appropriateness of the clinical space, in which 'noise', 'privacy' and the 'waiting area' were subthemes. The second was communication with staff, including subthemes of 'wanting more information' and a 'desire to be more involved'. Clinical implications: Liaison psychiatry services should consider appropriateness of the clinical space, promoting improved communication between staff and patients' companions, and a review of the information provided to companions in the emergency department. This research offers a novel perspective on liaison psychiatry and will enhance current understanding and clinical practice. Declaration of interest: None.